The The handwriting of society on the landscape: modeling of the Environmental Changes on the Borders of Protected Areas located in the Espinhaço Mountain Range, state of Minas Gerais, Brazil - Pimenta Ribeiro, Ana; Drummond, José Augusto; Magalhães Ribeiro, Eduardo (Sustainability in Debate, 2020)
This paper analyzes the contexts of the creation of two protected areas located on the Espinhaço Mountain Range, in the state of Minas Gerais (Brazil): Rio Preto State Park and Serra Negra State Park. It compares the social and natural contexts of the creation process of both protected areas between the years 1986 and 2009. To this end, we sought to understand the patterns of natural resources use by local populations, relating them to the outcomes of land use dynamics over time, identified through monitoring with orbital imagery images and through environmental modeling. Regarding land use analysis, changes in the landscape around the Rio Preto State Park corroborated field surveys, which registered an increase in the local population’s perception of environmental problems and in the inspection after the park’s creation. No relevant relation was found for the Serra Negra State Park. Environmental modeling of the Rio Preto State Park recorded a positive result in terms of environmental protection, because a trend of natural resource degradation was contained after the park’s creation. For the Serra Negra State Park, although protection of the area did not influence landscape changes, the dynamics of resource use by the local population did not degrade the natural environment.